Uwarunkowania demograficzne, formalnoprawne i ekonomiczne II filaru polskiego systemu emerytalnego - Obidziński, Piotr; Kamińska, Magdalena (Demographic, legal and economic conditions of the second pillar of Polish retirement system, 2006)
Subject of this paper is demographic, legal and economic conditions to functioning Open Pension Funds, being one of retirement claims source. The goal of the paper is simulation the impact of determinant: • demographic (life expectancy for woman and man), • legal (retirement age for woman and man), • economical (economical position of woman and man on the labor market), • relevant to choice of the Fund, on differences in future retirement claims descended from the second pillar.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 359-368